Dendronized‐Polymer Disturbing Cells' Stress Protection by Targeting Metabolism Leads to Tumor Vulnerability. Issue 14 (21st February 2020) - Pan, Dayi; Zheng, Xiuli; Zhang, Qianfeng; Li, Zhiqian; Duan, Zhenyu; Zheng, Wen; Gong, Meng; Zhu, Hongyan; Zhang, Hu; Gong, Qiyong; Gu, Zhongwei; Luo, Kui
Abstract: Metabolic demand of cancer is quite unique compared to normal tissues and this is an emerging hallmark of cancer, which brings a potential opportunity to discover drugs that target cancer cell metabolism. Herein, the development of a dendronized pyropheophorbide a (Ppa)‐conjugated polymer (DPP) is reported, and a linear Ppa‐conjugated polymer (LPP) is reported as a control. DPP is found to disturb cellular metabolism including increased energy depletion, dysfunctional H + regulation, and decreased antioxidation, resulting in deficiency in protecting cells from stresses. These vulnerable cells are subjected to photodynamic therapy (PDT) treatment in the presence of DPP, resulting in attenuated cancer cell growth and eventually cell death. The in vivo anticancer efficacy is also ascribed to significantly prolonged blood circulation and enhanced tumor accumulation of DPP due to its unique molecular structure. This study presents a new platform using dendronized polymers for tumor suppression by targeting cancer cell metabolism. Abstract : A novel dendronized‐polymeric nanostructure is introduced, which not only delivers a therapeutic agent for photodynamic therapy, but also intervenes in the metabolic pathways of tumor cells to incapacitate the protection mechanisms for their adaptation and survival. This study represents a new potential platform based on dendronized polymers that target cancer cell metabolism for tumor suppression.